Perceptions, barriers, and aspirations: understanding Grade 9 girls’ interest in STEM through three-day enrichment programs - Choudhary, Rahul; Parappilly, Maria; Woodman, Richard (Frontiers in Education, 2025)
The underrepresentation of women in university science programs highlights the need to understand factors influencing schoolgirls’ Science, Technology, Engineering, and Mathematics (STEM) career choices. We applied the socio-cognitive career theory (SCCT) model and a structured STEM enrichment framework to design a three-day intervention for Grade 9 female students. The intervention included presentations by female role models, hands-on STEM workshops, and industry immersion tours. This study explored the students’ aspirations and perceptions toward STEM as an educational subject and/or career, both before and after their exposure to the intervention. Data were obtained via structured and unstructured career interest surveys. Analyses included association analysis and factor analysis of quantitative data, and thematic analysis of qualitative data for N = 337 subjects. Factor analysis revealed “Barriers and Enablers” and “STEM Career Interest” as two key constructs driving the observed changes. Confidence in STEM abilities (factor loadings >0.70) and financial concerns (0.78) emerged as strong influences in the first group, while high loadings for enjoyment of STEM careers (0.84) and interest in further STEM studies (0.72) were observed in the second. Engineering and sustainability workshops were particularly effective in increasing interest in STEM careers. The thematic analysis provided complementary findings suggesting that a multifaceted approach is required to fully understand the reasons for improving confidence and aspirations toward STEM as a career. These findings suggest that barriers to participation are diverse but can be addressed through well-designed STEM enrichment activities, which effectively increase interest in STEM careers among 13–14-year-old girls.